EUFEMISME DALAM TUTURAN MASYARAKAT AIR TIRIS - Fauzan, Khairil; Sinaga, Mangatur; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact : The main objective of this study was to discuss the eufemism of the uttereances in Air Tiris society. In this research, the data of this reasearchwas the society who lived in Air Tiris. The data that writer has writen in this research was the sentences in containing eufemism. The data colletion techniqe about the eufemism of the utterances in Air Tiris Society was collected by interviw technique and recording technique by searching for sentences that use eufemism in the utterances of Air Tiris society. This method is operationalized by collecting the the data that is relevant to the writing problem. The data analysis technique . the descrivtive analysis technique is used to describe from and function of eufemism of the utterances in Air Tiris society. The data if this study amounted to 30 data which consist of 7 data in the words form, 17 data in the phrases form, 4 data in the clauses and 4 data avoiding words that are considered normal, 9 data to cover shyness, 1 data showed that he is an educated person and and 16 data avoided words that sound less good.Key words: eufemism